2011
DOI: 10.1371/journal.pone.0022373
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Spending and Resource Allocation to HIV Programs and Services in Latin America and the Caribbean

Abstract: BackgroundAn estimated 1.86 million people are living with HIV in Latin America and the Caribbean (LAC). The region is comprised of mainly middle-income countries with steady economic growth while simultaneously there are enormous social inequalities and several concentrated AIDS epidemics. This paper describes HIV spending patterns in LAC countries including analysis of the levels and patterns of domestic HIV spending from both public and international sources.Methods and FindingsWe conducted an extensive ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…8 Panama ranked above average in the region in prioritising domestic resources to AIDS treatment and HIV prevention. 11 While it is possible our findings are reflective of the HIV epidemic stabilising from 2001 to 2009 in Central and South America, and an increased public spending on HIV prevention and treatment programmes in the region, the difference in our findings from the previous study is possibly the result of differing sampling methodologies, TSS versus cluster sampling. 2 11 As reported previously in Panama, the prevalence of HIV and STIs varied widely by sex worker registration status.…”
Section: Discussionmentioning
confidence: 52%
“…8 Panama ranked above average in the region in prioritising domestic resources to AIDS treatment and HIV prevention. 11 While it is possible our findings are reflective of the HIV epidemic stabilising from 2001 to 2009 in Central and South America, and an increased public spending on HIV prevention and treatment programmes in the region, the difference in our findings from the previous study is possibly the result of differing sampling methodologies, TSS versus cluster sampling. 2 11 As reported previously in Panama, the prevalence of HIV and STIs varied widely by sex worker registration status.…”
Section: Discussionmentioning
confidence: 52%
“…It has been shown that in spite of the fact that the HIV epidemic in Latin America is driven by MSM and sex workers, the majority of prevention spending is not targeted at these groups [19]. At the country level, benefit-incidence analyses (BIA) have the potential to complement resource tracking activities by analyzing who benefits from using health services.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating resource allocation for HIV, demonstrated that in the 23 countries reporting data, 75% of expenses go to treatment and care while only 15% go to prevention. Moreover, of the 12 countries reporting investments in prevention, only Peru reported more than 5% of HIV prevention funding directed towards MSM prevention activities (52). The funding mismatch regarding treatment and prevention and regarding appropriate targeting of prevention activities to those key populations with the highest vulnerabilities needs to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Universal access to treatment has been achieved in Brazil, Costa Rica and Mexico (95). Funding for ART in LAC is mainly through domestic resources (52). The scale up of treatment in the region has been achieved due to decentralization, community programs, price negotiations, and expanding local production and distribution of ART drugs (95).…”
Section: Introductionmentioning
confidence: 99%